CRIMINAL LAW POLICY ON THE PROCESS OF FILING PRE-TRIAL APPEALS IN CASES OF DETERMINATION OF SUSPECTS BY INVESTIGATORS - Apdiansyah, Muhammad; Soponyono, Eko (Jurnal Hukum Khaira Ummah, 2024)
Pretrial aims to supervise law enforcement officers so that they do not abuse their authority. Regulated in the Criminal Procedure Code, this supervision is important even though it is automatically attached to the institution where the law is based. This ensures that tasks are carried out in accordance with the rules and authority. This study aims to examine in depth the pretrial process in cases of suspect determination. The main focus of this study is to analyze the judge's considerations in deciding pretrial cases, as well as the concept of legal certainty in the context of pretrial determination of suspects. This study uses a normative approach with a descriptive-analytical method. The data used include primary and secondary data obtained through interviews and literature studies. Data analysis was carried out qualitatively using the theory of law enforcement and the theory of legal responsibility. The results of the study indicate that the criminal law policy related to pretrial in cases of suspect determination is currently still limited to the provisions of the Criminal Procedure Code, especially Article 77. This study found that judges in deciding pretrial cases use certain arguments as the basis for consideration. In addition, this study also discusses the concept of legal certainty in pretrial determination of suspects and the possibility of other legal remedies outside the provisions of the Criminal Procedure Code that can be taken by the parties. Finally, this study identifies the problems and criminal law policies related to the pretrial motion submission process in the future.